A colônia agrícola nacional de Goiás e a redefinição nos usos do território / The National Agricultural Colony of Goiás and the redefinition in the uses of territory - Wagner Abadio de Freitas; Marcelo de Mello (Sociedade & Natureza)
The speech of March to the West produced by the New State was materialized with effective actions. The settlement, the occupation of the interior of the country and the creation of a minimal infrastructure were not only necessary but fundamental for the penetration of the capital and the production in the territory. This perspective, this research tried to understand the process of creation of the National Agricultural Colonies, their regional dynamics, the technical advances and the results produced by them. The emphasis was associated with the National Agricultural Colony of Goiás, considering the design of the occupation of Goiano territory and the production process, based on natural issues in the region “Mato Grosso de Goiás” and the insertion on engineering systems (infrastructure) that allowed different uses, whose materiality defined the form and content of the space produced from technical means. This work was structured based on the analysis of decrees and theoretical frameworks relevant to the topic, in order to establish a way that can contribute to understand the investigated process.